Sensitivity of arterial spin labeling perfusion MRI to pharmacologically induced perfusion changes in rat kidneys. Issue 4 (6th May 2014) - Tan, Huan; Thacker, Jon; Franklin, Tammy; Prasad, Pottumarthi V.
<x xml:space="preserve">Abstract</x> Purpose To investigate whether arterial spin labeling (ASL) MRI is sensitive to changes by pharmacologically induced vasodilation and vasoconstriction in rat kidneys. Materials and Methods Changes in renal cortical blood flow in seven rats were induced by adenosine infusion (vasodilation) and L‐NAME injection (vasoconstriction). All imaging studies were performed on a 3 Tesla scanner using a FAIR‐TrueFISP sequence for the ASL implementation. The acquisition time for each ASL scan was 6 min. Cortical perfusion rates were calculated using regions of interest analysis, and the differences in perfusion rates during baseline, vasodilation, and vasoconstriction were compared and assessed for statistical significance. Results Compared with the baseline, an average of 94 mL/100 g/min increase and 157 mL/100 g/min decrease in cortical perfusion was observed following adenosine infusion and L‐NAME administration, respectively. The changes in cortical perfusion were significant between baseline and vasodilation (P < 0.05), baseline and vasoconstriction (P < 0.01), and vasodilation and vasoconstriction (P < 0.01). Conclusion ASL is sensitive to pharmacologically induced perfusion changes in rat kidneys at doses comparable to current use. The preliminary results suggest the feasibility of ASL for investigating renal blood flow in a variety of rodent models. J. Magn. Reson. Imaging 2015;41:1124–1128. © 2014 Wiley Periodicals, Inc.